Role of Wnt/beta-catenin pathway in the nucleus accumbens in long-term cocaine-induced neuroplasticity : a possible novel target for addiction treatment - Cuesta, Santiago (2016)
Fil: Fil: Cuesta, Santiago. Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET); Argentina.